2006
DOI: 10.1007/s10936-006-9030-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Language Immersion Education on the Preattentive Perception of Native and Non-native Vowel Contrasts

Abstract: Proficiency in a second language (L2) may depend upon the age of exposure and the continued use of the mother tongue (L1) during L2 acquisition. The effect of early L2 exposure on the preattentive perception of native and non-native vowel contrasts was studied by measuring the mismatch negativity (MMN) response from 14-year-old children. The test group consisted of six Finnish children who had participated in English immersion education. The control group consisted of eight monolingual Finns. The subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
2
24
2
Order By: Relevance
“…This picture is consistent with earlier studies on Finnish children participating in English immersion education and on advanced adult classroom Finnish learners of English (Peltola et al, 2003, 2007) where no MMN traces were found for the development of a new L2 vowel category. Also, the same scenario emerged in studies on limited passive training (Dobel et al, 2009) where MEG data showed that L1 phonemic categories are powerful attractors in that they absorb the non-native stimulus, which is a considerable stumbling block on the path to the mastery of non-native contrasts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This picture is consistent with earlier studies on Finnish children participating in English immersion education and on advanced adult classroom Finnish learners of English (Peltola et al, 2003, 2007) where no MMN traces were found for the development of a new L2 vowel category. Also, the same scenario emerged in studies on limited passive training (Dobel et al, 2009) where MEG data showed that L1 phonemic categories are powerful attractors in that they absorb the non-native stimulus, which is a considerable stumbling block on the path to the mastery of non-native contrasts.…”
Section: Discussionsupporting
confidence: 92%
“…These brain responses to new phonemes probably develop in children at a very fast pace: i.e., within three months of intensive exposure, as evidenced by MMN to L2 phoneme contrasts in Finnish children participating in French language immersion education (Cheour et al, 2002; Shestakova et al, 2003; Peltola et al, 2005). Again, however, subsequent works did not confirm these findings when the L2 was English both for Finnish listeners (Peltola et al, 2007) and Japanese listeners (Bomba et al, 2011). Finally, Rinker et al (2010) for bilingual Turkish–German kindergarten children growing up in Germany have shown that the MMN response is less robust in Turkish–German children to the German vowel, when compared to a German control group.…”
Section: Introductionmentioning
confidence: 91%
“…Training induced changes in goodness rating may demand a more hierarchically structured category which may develop slowly while discrimination sensitivity may arise prior to that. This has been suggested for memory trace formation as well (Peltola et al, 2007). Some sort of "high variability" training approach (see e.g., Bradlow, 2008), where the participants are exposed to a large set of varying stimuli from both categories, could be a better training method for creating a native-like hierarchical category.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of discrimination on immigrants' mental health has been addressed in previous studies [21,29]. Immigrants' experiences of discrimination in the pre-migration stage make them more vulnerable for the same processes in the post-migration phase.…”
Section: Discussionmentioning
confidence: 99%